PENGARUH STRESS KERJA, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS SOSIAL KOTA SEMARANG - lindasari, Kusnia; Yunianto, Askar (Proceeding SENDI_U, 2019)
This study aims to analyze the influence of work stress, work environment, and motivation on the performanceof employees of Dinas Sosial Kota Semarang. Types of data used are primary data is data obtained directlyfrom the original source of the questionnaire. Population in this research is employees of Dinas Sosial Kotasemarang. Sampling was done by proportional random sampling technique with a total sample 117respondents. The data collected were analyzed using factor analysis to test the validity of question items, thereliability testing using cronbach alpha, and hypothesis testing using multiple linear regression. Regressiontesting result show that there are negative significant influence of work stress on employee performance, thereare positive significant influence of work environment on employee performance, and there is positivesignificant influence of motivation to employee performance.Keywords: Work Stress, Work Environment, Motivation, and Employee Performance.